Global crises and reform of the international monetary system - Maria Socorro Gochoco-Bautista (University of the Philippines, School of Economics (UPSE), 2009)
History seems to have a tendency to repeat itself. The global economy goes through systemic crises. A few of these crises are catastrophic enough to seriously threaten global peace and stability. Yet it is precisely at historical junctures such as these that the inertia over reforming the international monetary system-the rules and institutions that govern international payments-is somehow overcome. World War I and the general return to the gold standard in the 1920s led to a shortage of gold from its undervaluation. This was corrected by an appreciation in its price engineered through the great deflation of the 1930s. The shock of World War II brought about the Bretton Woods Articles of Agreement. Pressure from a weak dollar in the 1970s helped create the European Monetary System. The first global crisis of the 21st century has turned out to be as severe as the Great Depression, and in some aspects, worse, though thankfully, not as long-lived. More importantly, its occurrence offers a rare opportunity to consider reforming the international monetary system yet again.
Keywords: 330; Weltwirtschaftskrise; Wirtschaftsgeschichte; Europäisches Währungssystem; Internationales Währungssystem